Identification of novel regulatory factor X (RFX) target genes by comparative genomics in Drosophila species. - Laurençon, A.; Dubruille, R.; Efimenko, E.; Grenier, G.; Bissett, R.; Cortier, E.; Rolland, V.; Swoboda, P.; Durand, B. (Genome Biology, 2007)
Regulatory factor X (RFX) transcription factors play a key role in ciliary assembly in nematode, Drosophila and mouse. Using the tremendous advantages of comparative genomics in closely related species, we identified novel genes regulated by dRFX in Drosophila.We first demonstrate that a subset of known ciliary genes in Caenorhabditis elegans and Drosophila are regulated by dRFX and have a conserved RFX binding site (X-box) in their promoters in two highly divergent Drosophila species. We then designed an X-box consensus sequence and carried out a genome wide computer screen to identify novel genes under RFX control. We found 412 genes that share a conserved X-box upstream of the ATG in both species, with 83 genes presenting a more restricted consensus. We analyzed 25 of these 83 genes, 16 of which are indeed RFX target genes. Two of them have never been described as involved in ciliogenesis. In addition, reporter construct expression analysis revealed that three of the identified genes encode proteins specifically localized in ciliated endings of Drosophila sensory neurons.Our X-box search strategy led to the identification of novel RFX target genes in Drosophila that are involved in sensory ciliogenesis. We also established a highly valuable Drosophila cilia and basal body dataset. These results demonstrate the accuracy of the X-box screen and will be useful for the identification of candidate genes for human ciliopathies, as several human homologs of RFX target genes are known to be involved in diseases, such as Bardet-Biedl syndrome.